Crown Ethers Enable Room Temperature Synthesized CsPbBr3 Quantum Dots for Light-Emitting Diodes - Veldhuis, Sjoerd Antonius (2018)
The synthesis of all-inorganic cesium lead halide perovskite quantum dots (QDs) typically requires high temperatures, stringent conditions, large quantities of surface ligands, and judicious purification steps to overcome ligand-induced charge injection barriers in optoelectronic devices. Low-temperature syntheses generally require lower ligand concentrations, but are severely limited by the low solubility of the Cs precursor. We describe an innovative and general approach under ambient conditions to overcome these solubility limitations, by employing crown ethers. The crown ethers facilitate complete dissolution of the CsBr precursor, rendering CsPbBr3 QD inks practical for device fabrication. The resultant LEDs displayed bright green emission, with a current efficiency, and external quantum efficiency of 9.22 cd A-1 and 2.64%, respectively. This represents the first LED based on CsPbBr3 QDs prepared at room temperature. Lastly, the crown ethers form core-shell structures, opening new avenues to exploit their strong coordination strength.